External apical root resorption after orthodontic treatment: analysis in different chronological periods - NEVES,Bruno Moreira das (2022)
ABSTRACT Introduction: External apical root resorption (EARR) is characterized by the definitive loss of tooth root structure, with a higher incidence in lateral and central maxillary incisors. Objective: To identify, in different chronological periods, the incidence of EARR in the maxillary incisors (MI) of patients orthodontically treated with or without premolars extraction. Methods: Periapical radiographs before and after orthodontic treatment of 1,304 MIs from 326 patients (205 women and 121 men) were evaluated for EARR, divided into five groups, according to the chronological period in which treatments were started: G90) from 1990 to 1994, G95) from 1995 to 1999, G00) from 2000 to 2004, G05) from 2005 to 2009, G10) from 2010 to 2015. The evaluation was performed in each group, in patients who underwent maxillary first premolars extraction and those who did not. For statistical analysis, Fisher’s exact test was used, with a significance level of p < 0.05. The EARR was measured using the adapted Levander and Malmgren classification. Results: Incidence of EARR was higher in MIs of patients treated with maxillary premolar extraction (p < 0.05) in two chronological periods (G00 and G10), also being influenced by orthodontic treatments with longer duration, and due to possible individual genetic factors. Conclusion: Even with the limitations of a retrospective study, the lack of a defined EARR pattern in the MIs at different chronological periods was larger in the experimental group, due to the sum of factors such as premolars extraction, prolonged orthodontic treatment, possible genetic characteristics, and root shape, without the influence of the sex and age.